2021
DOI: 10.1007/s11548-021-02320-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific plate for navigation and fixation of the distal radius: a case series

Abstract: Purpose Corrective osteotomy of a malunited distal radius conventionally relies on 2D imaging techniques for alignment planning and evaluation. However, this approach results in suboptimal bone repositioning, which is associated with poor patient outcomes. In this case series, we evaluate the use of novel patient-specific plates (PSPs), which feature navigation and fixation of bone segments as preoperatively planned in 3D. Methods Ten participants with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Only 3 case reports have documented the technique of printing titanium plates for stable fixation in corrective osteotomies of the radius and ulna. 10,13,14 These reports included 1, 5, and 7 cases, all of which resulted in satisfactory outcomes. Dobbe et al 10 also compared the 3-dimensional preoperative planning and intraoperative fixation with a patientspecific plate to conventional planning using 2dimensional images and standard plates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 3 case reports have documented the technique of printing titanium plates for stable fixation in corrective osteotomies of the radius and ulna. 10,13,14 These reports included 1, 5, and 7 cases, all of which resulted in satisfactory outcomes. Dobbe et al 10 also compared the 3-dimensional preoperative planning and intraoperative fixation with a patientspecific plate to conventional planning using 2dimensional images and standard plates.…”
Section: Discussionmentioning
confidence: 99%
“…Alignment is correlated to patient-reported and functional outcomes, which implies that 3dimensional preoperative planning and use of patient-tailored plates could potentially lead to better outcomes over traditional methods. 10,22 A biomechanical study showed that 3-dimensionally printed, volar-locking, titanium plates provided significantly higher stiffness compared with conventional distal radius plates. 23 Further comparative studies investigating the clinical outcomes after both methods are still required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations